2015
DOI: 10.4041/kjod.2015.45.2.82
|View full text |Cite
|
Sign up to set email alerts
|

A reliable method for evaluating upper molar distalization: Superimposition of three-dimensional digital models

Abstract: ObjectiveThe aim of this study was to evaluate the reliability of measurements obtained after the superimposition of three-dimensional (3D) digital models by comparing them with those obtained from lateral cephalometric radiographs and photocopies of plaster models for the evaluation of upper molar distalization.MethodsData were collected from plaster models and lateral cephalometric radiographs of 20 Class II patients whose maxillary first molars were distalized with an intraoral distalizer. The posterior mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…25 The conventional method to measure the amount of movement of the molars and incisors from distalization is to use lateral cephalometric radiographies and dental cast photocopies. 26 Cephalometric radiographs involve radiation and may cause errors in landmark identification because of superimpositions of symmetrical anatomic structures. 27 Three-dimensional evaluations cannot be performed alone in either method; therefore, these 2 methods should be used in combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 The conventional method to measure the amount of movement of the molars and incisors from distalization is to use lateral cephalometric radiographies and dental cast photocopies. 26 Cephalometric radiographs involve radiation and may cause errors in landmark identification because of superimpositions of symmetrical anatomic structures. 27 Three-dimensional evaluations cannot be performed alone in either method; therefore, these 2 methods should be used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to make a reliable and an accurate 3D evaluation of tooth movements with digital models alone. 26 It is reported that pretreatment and posttreatment digital models can be reliably aligned without the need for a reference plane using reverse engineering software and the best-fit mathematical superimposition method. 17 This method uses the iterative closest point algorithm and needs stable regions on different models for superimposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The angle formed by the intersection of these two lines was evaluated. 24 An increase of the angle indicated a distal rotation of the molar during treatment, and the decrease a mesial rotation.…”
Section: Digitized Models Analysismentioning
confidence: 99%
“…following an adapted method previously described. 24 A frontal plane, perpendicular to the sagittal plane, and passing through the most anterior point of the incisive papilla was constructed by the software on the digitized models to determine the sagittal changes presented by the incisors, canines, premolars and molars 24 ( Fig. 2A).…”
Section: Digitized Models Analysismentioning
confidence: 99%